Visible light photocatalytic degradation of dyes by bismuth oxide-reduced graphene oxide composites prepared via microwave-assisted method - Liu, Xinjuan (2013)
Bi2O3-reduced graphene oxide (RGO) composites were successfully synthesized via microwave-assisted reduction of graphite oxide in Bi2O3 precursor solution using a microwave system. Their morphologies, structures, and photocatalytic performance in the degradation of methylene blue (MB) and methyl orange (MO) were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction spectroscopy, UV–vis absorption spectroscopy, and electrochemical impedance spectroscopy, respectively. The results show that the RGO addition can enhance the photocatalytic performance of Bi2O3–RGO composites. Bi2O3–RGO composite with 2 wt.% RGO achieves maximum MO and MB degradation rates of 93% and 96% at 240 min under visible light irradiation, respectively, much higher than those for the pure Bi2O3 (78% and 76%). The enhanced photocatalytic performance is ascribed to the increased light adsorption and the reduction in electron–hole pair recombination in Bi2O3 with the introduction of RGO.